Malignant Mesothelioma - L. Pouliquen, Daniel; Kopecka, Joanna (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Malignant mesothelioma (MM) is a rare and aggressive cancer, related to chronic inflammation and oxidative stress caused mainly by exposure to asbestos. Although this mineral has been banned for decades in many countries, epidemiologists predict the MM epidemic will last past 2040, raising many concerns in public health given its late diagnosis, dismal prognosis, and lack of current efficient therapies.To deal with this situation, important breakthroughs have recently been made in the understanding of MM's complex biology and the carcinogenic process of the different patterns of the disease. Examples of these include the development of new biomarkers and the deciphering of gene-environment interactions, molecular mechanisms of invasiveness, deregulated pathways, altered expression of miRNAs, DNA damage repair, or metabolic profile. From now on, MM's aggressive and chemoresistant character appears linked to a polyclonal malignancy, and heterogeneity in molecular alterations.Given these improvements, new therapeutic targets are being explored to solve the double challenge faced by clinicians. The first is to reduce tumor development and its wasting consequences as soon as possible, without resistance and with limited toxicity. The second is to stimulate the recognition of tumor cells by the induction of a specific immune response. This Special Issue will highlight all these aspects.